Bahasa Indonesia Sebagai Kiblat Bahasa Kepariwisataan Domestik Indonesia - Sufa, Laisya Failah (Politeknik Pariwisata Medan, 2024)
By strengthening the role of Bahasa Indonesia in the tourism industry, Indonesia can enhance the traveler experience, expand its tourism market, and promote its rich culture and nature to the world. Thus, providing basic information in Bahasa Indonesia in popular tourist destinations can help foreign tourists to better interact with their surroundings, even though Bahasa Indonesia is not the primary foreign language for most international tourists. The research method used in this research is literature review or literature study. Indonesian has a positive value for the world of Indonesian tourism such as the development of vocabulary use. But on the one hand it has a negative value, namely the non-optimal function of Indonesian as a means of disclosing tourism industry products in Indonesia. In this case, it needs help from various parties such as the government in order to implement the use of Indonesian in the tourism industry in Indonesia.